Betibeglogene autotemcel gene therapy for non–β0/β0 genotype β-thalassemia - Franco Locatelli (2022)
BACKGROUND Betibeglogene autotemcel (beti-cel) gene therapy for transfusion-dependent β-thalassemia contains autologous CD34+ hematopoietic stem cells and progenitor cells transduced with the BB305 lentiviral vector encoding the β-globin (βA-T87Q) gene. METHODS In this open-label, phase 3 study, we evaluated the efficacy and safety of beti-cel in adult and pediatric patients with transfusion-dependent β-thalassemia and a non–β0/β0 genotype. Patients underwent myeloablation with busulfan (with doses adjusted on the basis of pharmacokinetic analysis) and received beti-cel intravenously. The primary end point was transfusion independence (i.e., a weighted average hemoglobin level of ≥9 g per deciliter without red-cell transfusions for ≥12 months). RESULTS A total of 23 patients were enrolled and received treatment, with a median followup of 29.5 months (range, 13.0 to 48.2). Transfusion independence occurred in 20 of 22 patients who could be evaluated (91%), including 6 of 7 patients (86%) who were younger than 12 years of age. The average hemoglobin level during transfusion independence was 11.7 g per deciliter (range, 9.5 to 12.8). Twelve months after beti-cel infusion, the median level of gene therapy–derived adult hemoglobin (HbA) with a T87Q amino acid substitution (HbAT87Q) was 8.7 g per deciliter (range, 5.2 to 10.6) in patients who had transfusion independence. The safety profile of beti-cel was consistent with that of busulfan-based myeloablation. Four patients had at least one adverse event that was considered by the investigators to be related or possibly related to beti-cel; all events were nonserious except for thrombocytopenia (in 1 patient). No cases of cancer were observed. CONCLUSIONS Treatment with beti-cel resulted in a sustained HbAT87Q level and a total hemoglobin level that was high enough to enable transfusion independence in most patients with a non–β0/β0 genotype, including those younger than 12 years of age. (Funded by Bluebird Bio; HGB-207 ClinicalTrials.gov number, NCT02906202.).